2013
DOI: 10.3390/ijms141122642
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Non-Coding RNA Regulation in Abiotic Stress Responses

Abstract: Plant growth and productivity are largely affected by environmental stresses. Therefore, plants have evolved unique adaptation mechanisms to abiotic stresses through fine-tuned adjustment of gene expression and metabolism. Recent advanced technologies, such as genome-wide transcriptome analysis, have revealed that a vast amount of non-coding RNAs (ncRNAs) apart from the well-known housekeeping ncRNAs such as rRNAs, tRNAs, small nuclear RNAs (snRNAs) and small nucleolar RNAs (snoRNAs) are expressed under abioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 78 publications
0
36
0
Order By: Relevance
“…Emerging evidence has revealed that ncRNAs are major products of the plant transcriptome (Rymarquis et al, 2008). They may have significant regulatory importance, especially during stress situations (Matsui et al, 2013). In this study, the perfect or near-perfect match to target sites allowed effective in silico prediction of the target sequences (Rhoades et al, 2002) and revealed that 10 miRNA targeted cold-responsive genes.…”
Section: Discussionmentioning
confidence: 97%
“…Emerging evidence has revealed that ncRNAs are major products of the plant transcriptome (Rymarquis et al, 2008). They may have significant regulatory importance, especially during stress situations (Matsui et al, 2013). In this study, the perfect or near-perfect match to target sites allowed effective in silico prediction of the target sequences (Rhoades et al, 2002) and revealed that 10 miRNA targeted cold-responsive genes.…”
Section: Discussionmentioning
confidence: 97%
“…Although the function of the majority of ncRNAs is still unknown, current evidences suggest the significance of ncRNAs in plant development and response to environmental stresses (Matsui et al 2013). Based on the expression profiles and predicted functions, ncRNAs can be subdivided into housekeeping ncRNAs and regulatory ncRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…These also include promoter and enhancer regions and other 3 0 -and 5 0 untranslated regions (UTRs) of genes (Nie et al 2012;Liu et al 2012). lncRNAs can be transcribed in either the sense or antisense direction (Nie et al 2012;Matsui et al 2013). Although the functions of various lncRNA remain largely unknown, there is evidence that a number of lncRNA may be involved in regulating transcription (Ponting et al 2009).…”
Section: Introductionmentioning
confidence: 96%
“…The first includes ncRNAs that have general housekeeping functions and these include ribosomal RNA (rRNA), transfer RNA (tRNA) and small nuclear/small nucleolar RNA (sn/ snoRNA). The second category includes microRNA (miRNA), small interfering RNA (siRNA) and long noncoding RNA (lncRNA) that have regulatory roles in plants for diverse cellular processes such as nutrient homeostasis (Sunkar et al 2007), growth, development and differentiation (Ben Amor et al 2009) and abiotic stress response (Sunkar et al 2007;Matsui et al 2013). A number of microRNAs are known to be related to drought stress.…”
Section: Introductionmentioning
confidence: 99%